Coronary thrombosis in a young male with COVID-19 - Abdullah Shams (14136646) (2020)
COVID-19 predominantly presents with respiratory symptoms, but other presentations are reported, including cardiac manifestations and thromboembolism. We present a healthy young gentleman with COVID-19 pneumonia, who developed acute ST-segment elevation myocardial infarction (STEMI) due to coronary thrombosis. He was managed successfully by primary percutaneous coronary intervention (PPCI). Other Information Published in: IDCases License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.idcr.2020.e00923